A T0/Trigger detector for the External Target Experiment at CSR. (14th June 2017) - Hu, D.; Shao, M.; Sun, Y.; Li, C.; Chen, H.; Tang, Z.; Zhang, Y.; Zhou, J.; Zeng, H.; Zhao, X.; You, W.; Song, G.; et al.
Abstract: A new T0/Trigger detector based on multi-gap resistive plate chamber (MRPC) technology has been constructed and tested for the external target experiment (ETE) at HIRFL-CSR. It measures the multiplicity and timing information of particles produced in heavy-ion collisions at the target region, providing necessary event collision time (T0) and collision centrality with high precision. Monte-Carlo simulation shows a time resolution of several tens of picosecond can be achieved at central collisions. The experimental tests have been performed for this prototype detector at the CSR-ETE. The preliminary results are shown to demonstrate the performance of the T0/Trigger detector.